Prognostic Predictors of Endodontic Microsurgery: Radiographic Assessment - Chaonan Su; Rui Zhang; Rong Wang; Chengcan Yang; Zan Wang; Liuyan Meng (Elsevier, 2022)
Objective: This study aimed to compare the healing outcomes of endodontic microsurgery (EMS) using 2-dimensional (2D) and 3-dimensional (3D) radiographic evaluation in a Chinese population. The prognostic factors of EMS were identified according to the 2D and 3D healing classifications. Materials and methods: The teeth (n = 82) were studied using 2D and 3D radiographic examinations. The 2D and 3D healing criteria were used to evaluate the healing outcome. Prognostic factors were investigated based on healing outcomes. Data were analysed using SPSS, and P < .05 was considered significant. Results: There were significant differences between 2D and 3D healing outcomes (P = .004). For the 3D images, age older than 45 years was found to be a significant negative predictor (P = .005). Conclusions: Cone-beam computed tomographic images provided more precise evaluation of periapical lesions and healing outcomes of EMS than conventional periapical radiographs. Age (>45 years) of the patients exhibited a significant influence on the healing outcome of EMS as determined using 3D images.